In Silico Analysis of the Interaction Between Stevia Compounds and the MGAM Receptor as Potential Antidiabetic Agents - Januarto, Januarto (Indonesian Journal of Pharmaceutical Education, 2025)
Diabetes mellitus is a chronic metabolic disease characterised by hyperglycaemia. Current treatments include pharmacological therapy, lifestyle modifications, and patient education. This study aimed to analyse the interaction of stevioside, a major compound from Stevia rebaudiana, with the MGAM receptor using Molegro Virtual Docker, compare its binding affinity and interaction pattern with those of acarbose and metformin, and identify its potential as an MGAM inhibitor. The methodology included protein and ligand preparation, physicochemical and toxicity prediction, and molecular docking simulations. Method validation was performed through redocking of the native ligand (acarbose), yielding a Root Mean Square Deviation (RMSD) of 1.75 Å, indicating high accuracy of the docking protocol. Docking results showed that the control ligand GLC-GLC-AC1(B) had the strongest binding affinity to MGAM (MolDock Score: –97.922), followed by metformin (MolDock Score: 89.506), while stevioside exhibited the weakest interaction (MolDock Score: 336.153). Despite some overlapping interactions with metformin, stevioside demonstrated a distinct binding mode and lower affinity, suggesting an alternative mechanism of action. Further experimental validation is necessary to confirm these computational findings and to explore the potential of stevioside as an antidiabetic agent.